Semantic Clustering during Verbal Episodic Memory Encoding and Retrieval in Older Adults: One Cognitive Mechanism of Superaging - Clare Shaffer; Joseph M. Andreano; Alexandra Touroutoglou; Lisa Feldman Barrett; Bradford C. Dickerson; Bonnie Wong (Brain Sciences, 2024)
Normal aging is commonly accompanied by a decline in cognitive abilities, including memory, yet some individuals maintain these abilities as they get older. We hypothesize that semantic clustering, as an effective strategy for improving performance on episodic recall tasks, may contribute to the maintenance of youthful memory in older adults. We investigated the dynamics of spontaneous production and utilization of the semantic clustering strategy in two independent samples of older adults who completed a list learning paradigm (N1 = 40 and N2 = 29, respectively). Specifically, we predicted and observed that older adults who spontaneously used a semantic clustering strategy throughout the encoding process learned more words by the culmination of the encoding trials (Sample 1, R2= 0.53, p < 0.001; Sample 2, R2= 0.51, p < 0.001), and that those who utilized this strategy during retrieval recalled more words, when compared to older adults who did not produce or utilize a semantic clustering strategy during both a short (Sample 1, R2 = 0.81, p < 0.001; Sample 2, R2 = 0.70, p < 0.001) and long delay retrieval (Sample 1, R2 = 0.83, p < 0.001; Sample 2, R2 = 0.77, p < 0.001). We further predicted and observed that older adults who maintained a youthful level of delayed free recall (i.e., “Superagers”) produced (Sample 1, F(1, 38) = 17.81, p < 0.0001; Sample 2, F(1, 27) = 14.45, p < 0.0001) and utilized (Sample 1, F(1, 39) = 25.84, p < 0.0001; Sample 2, F(1, 27) = 12.97, p < 0.01) more semantic clustering than did older individuals with normal memory for their age. These results suggest one cognitive mechanism through which Superagers maintain youthful memory function and raise the possibility that older adults may be able to train themselves to use strategies to promote better memory.